THE INFLUENCE OF CHANGE MANAGEMENT AND ORGANIZATIONAL CULTURE TO EMPLOYEE PERFORMANCE STUDY AT SAM RATULANGI UNIVERSITY RECTORATE - Lumunon, Dwiranni F.; Rumokoy, Farlane S.; Tumiwa, Johan . (Universitas Sam Ratulangi, 2017)
Abstract: This research titled: The Influence Of Change Management And Organizational Culture To Employee Performance Study At Sam Ratulangi University Rectorate. This study aims to determine the impact of change management and organizational culture on employee performance simultaniously and partially. Total sample are 75 respondents. The research was conducted at Sam Ratulangi University Rectorate office in Manado City North Sulawesi Province. Data analysis using multiple linear regression analysis, t test and F test. The results showed that, change management has significant and positive impact on employee performance, change management become the highest impact factor to employee performance compare other variable in this research. Organizational culture has significant and positive impact on employee performance, organizational culture become the lowest impact factor to employee performance compare other variable. Suggestion of this research is Sam Ratulangi University in order to improve the employee performance of this organization should focus first of all on the change management also the organizational culture as the proxy of employee performance.Â Keywords: change management, organizational culture, employee performance